Correction: Firearm-related experiences and perceptions among United States male veterans: A qualitative interview study - Simonetti, Joseph A.; Dorsey Holliman, Brooke; Holliday, Ryan; Brenner, Lisa A.; Monteith, Lindsey L. (PloS one, 2020)
[This corrects the article DOI: 10.1371/journal.pone.0230135.].